JESUS AND ELVIS ; CREATIVE RESOURCES FOR USE IN SCHOOLS AND CHURCHES - McTavish, John (RESOURCE PUBLICATIONS, 2020)
Jesus and Elvis offers a host of creative resources for use in schools and churches. Jesus proclaims the book's unabashed gospel-centered content, Elvis its unapologetic creative style. The book as a whole should appeal to both the young and the old, wide-eyed seekers, battle-scarred churchgoers, really anyone short of the musclebound atheist or bigoted believer. Categories include poems, plays, hymns, prayers, pictures, a communion service, participatory readings, and essays. -- back cover.